Mechanism of ultrasonic field on the particle micro-agglomeration and interfacial bonding of SiCp/7085 composites - WANG Kun; ZHANG Li-hua; LI Zheng-hua; JIANG Wen; LI Chang-zi (工程科学学报)
SiCp/7085 composites with 10% particle volume fraction was prepared by a semi-solid mixture-mechanical stirring-ultrasound vibrations method. The particle distribution and interface bonding were studied through optical microscopy (OM), scanning electron microscopy (SEM) and X-ray diffraction (XRD), and the effect of ultrasonic field on the particle agglomeration and interfacial bonding of the composites was studied emphatically. The experimental results indicate that the effect of mechanical stirring on the agglomeration and interfacial bonding of 400 mesh particles is not significant. Under ultrasonic field, the coating of particles agglomeration can be effectively get rid of by instantaneous high pressure and temperature and micro jet induced by cavitation. That ultrasonic gets rid of the oxide film on the particle surface, removes the gas layer and makes magnesium in melt contact with particles directly is a very important factor in improving wettability between melt and particles. Finally, the MgAl2O4 strengthening phase is formed at the interface and a better interface bonding is got.